2009
DOI: 10.1186/1478-4491-7-59
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and communication needs assessment of community health workers in a developing country: a qualitative study

Abstract: Background: Primary health care is a set of health services that can meet the needs of the developing world. Community health workers act as a bridge between health system and community in providing this care. Appropriate knowledge and communication skills of the workers are key to their confidence and elementary for the success of the system. We conducted this study to document the perceptions of these workers on their knowledge and communication needs, image building through mass media and mechanisms for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
(10 reference statements)
0
38
0
1
Order By: Relevance
“…A 2007 study by Constella Futures in Uttar Pradesh, India, concluded that the biggest source of health messages for auxiliary nurse midwives (85%) and anganwadi workers (64%) was television. A study conducted in Pakistan also reported broadcast media, especially television, as a credible source of health information for health workers . Similarly, in a study conducted in Malawi, face‐to‐face communication was found to be the most preferred method of sharing knowledge and information among health workers .…”
Section: Discussionmentioning
confidence: 99%
“…A 2007 study by Constella Futures in Uttar Pradesh, India, concluded that the biggest source of health messages for auxiliary nurse midwives (85%) and anganwadi workers (64%) was television. A study conducted in Pakistan also reported broadcast media, especially television, as a credible source of health information for health workers . Similarly, in a study conducted in Malawi, face‐to‐face communication was found to be the most preferred method of sharing knowledge and information among health workers .…”
Section: Discussionmentioning
confidence: 99%
“…19 Updating the knowledge and communication skills of CHW’s in developing countries is valuable in enhancing their credibility as health educators. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Presently, there are 100,000 LHWs employed in the community[14]. The LHWs are females with a minimum of eight years of education, residents of the locality in which they are working.…”
Section: Methodsmentioning
confidence: 99%